Epidemiological analysis of the profile of deaths due to trauma in motorcycle accidents in the state of Pará between 2018 and 2022 (Research, Society and Development, 2023)
Introduction: Land transport accidents represent one of the main causes of death in Brazil, so motorcyclists are the main victims of these accidents. This is due to the specific characteristics of this type of vehicle that guarantee a high morbidity and mortality rate for this specific group. Objective: To analyze the epidemiological profile of fatal traffic accidents involving motorcyclists in Pará, between 2018 and 2022. Methodology: It is an observational, retrospective, quantitative and descriptive study, using data obtained from the Notifiable Diseases Information System (SINAN), presenting mortality due to trauma in motorcycle accidents in the state of Pará as the object of analysis. Results: During this period, 707 deaths caused by trauma in accidents involving the use of motorcycles in Pará were documented. deaths in males (81.2%), in the age group of 20 to 29 years (28.9%) and in individuals of mixed race (91.2%), and most of these deaths occurred in Metropolitan Region I (27 .4%). Conclusion: The data obtained allows a more detailed understanding of the profile of the victims and the possible risk factors involving accidents caused by the use of motorcycles, such as the use of helmets, alcohol abuse, and the COVID-19 pandemic, being This information is useful for formulating more effective prevention and awareness measures.